Calculation of queue formation and queue length at airport check-in counters - Petr Had; Jiří Volt; Slobodan Stojić (Acta Polytechnica CTU Proceedings)
This paper focuses on calculation of airport passenger queue formation and its length. The main goal of the paper is to evaluate the appropriateness of the combination of machine learning and determistic algorithm for queue length determination. The study focuses on the departing passenger flows to the check-in counters. In this study the Random Forest algorithm was applied for passenger number prediction, and followed by application of the deterministic algorithm for passenger queue length estimation. The study was performed using the real data from the Václav Havel Airport Prague operations. Presented results indicate that the combined approach of machine learning and a deterministic algorithm offers useful insights into passenger queue formation. This approach provides valuable insights into queue dynamics at check-in counters, enabling improvements in planning and management of airport operations during operational peak.